Teen Dating Violence Victimization: Associations Among Peer Justification, Attitudes Toward Gender Inequality, Sexual Activity, and Peer Victimization - Hunt, Kristen E. (Journal of interpersonal violence, 2022)
The current study, grounded in a social learning theoretical framework, examined attitudes and behaviors associated with verbal and physical teen dating violence (TDV) victimization. Because TDV varies by gender in both frequency and severity, these associations were examined first within the overall sample, and then by gender to further investigate these differences. A total of 1,884 adolescents (49.2% boys; 50.8% girls; average age 14.79 years; SD = .58) who reported ever dating someone were included in the analysis. Specifically, peers’ justification of TDV, attitudes supporting gender inequality, sexual activity, and peer victimization were included to determine their cross-sectional association with verbal and physical TDV victimization. Data were analyzed separately for boys and girls. Results indicated that peers’ justification of TDV, peer victimization, sexual activity, and attitudes supporting gender inequality were each associated with higher physical and verbal TDV victimization for girls and boys. Most of these factors remained significant when separated by gender, except for sexual activity and attitudes supporting gender inequality, which were not associated with physical TDV victimization for boys and girls, respectively. Implications for practice and research are discussed.